(untitled) (GEOmedia, 2009)
Geospatial design: Autodesk’s vision between integration and convergence For 25 years, Autodesk has been a key partner to federal, state, and local governments delivering precision data, products, and tools that support mission-critical objectives. Whether the need is to create, manage, share, or visualize data”from one source or many”Autodesk solutions allow state and local governments, transport and telecommunication companies to work smarter, faster, and more efficiently. Autodesk software provides practical mapping functionality to engineers and geospatial professionals who need an open, flexible way to integrate CAD and GIS data throughout the organization and help them get the full value from existing data and reduces costs of disseminating spatial information to customers, internal teams, the public, and other enterprise applications.